(In)visibilidade do trabalho docente nas escolas estaduais de Uberlândia-MG - Pisani, Mariane Gabrielle Rodrigues da Silva (2022)
This research at Master Degree level is part of the Knowledge and Educational Practices research line of the Post-graduate Program in Education - PPGED/UFU and its object of study is to understand the historical process of precariousness and degradation of teaching. Under this perspective it was essential to understand the teaching process deeply, its practice and also its identity (dis)configuration. The main question which guided our discussions was: What are the meanings and reverberations of the historical-political-social process of precariousness of teaching work within the context of the Public State School in Uberlândia-MG, having the (in)visibility and the degradation of the teacher's identity as implication? Concerning methodology the research is exploratory in nature, has a qualitative approach and is also a bibliographic review. The discussion was built and based on the process of precariousness and degradation of teaching and the bibliographic review was subsidized by the State of the Question technique and by Freire (1993, 2000, 2014; 2018), Arroyo (2000; 2014), Nóvoa (2014), Orlandi (2007), Tardif & Lessard (2014) and Silva (2020). As for data collection a structured questionnaire, in the Google Forms version, was sent by e-mail to 120 Elementary School teachers from the 1st to the 9th grades from the State Network of Uberlândia-MG and a total of 50 questionnaires were answered. Data analysis followed the Content Analysis proposed by Bardin (2011). From the dialogue established with the participants we visualize there is awareness of the procedural historicity of precariousness and degradation of the teaching work. However a vocational ideology can also be mentioned. It is important to observe that not everyone understands teaching as a specific profession with sociopolitical commitment and responsibility. The fragmentation and invisibility of teachers can be understood and highlighted based on arguments of the participants, as well as the process of self-silencing and coercive silencing of the political and human voice of teachers. Physical and psychological illnesses were also reported exposing their fragility as human beings. It can also be told that the participant teachers of this study are eager to take part of teacher training courses that favor collaboration among teachers. Based on Freire it can be understood that improving the quality of education requires permanent and intentional training of teachers. Thus there is a need to provide spaces for dialogue and learning, exchanges and re-signification of experiences, strengthening the identity of teachers and educators.